Désobéissance radicale, désobéissance politique : la remise en cause du consensus rawlsien dans le champ philosophique étatsunien contemporain - Charlotte Thomas-Hébert (Amnis)
Starting in the early 2010s with Occupy Wall Street, sustained by Black Lives Matter, and galvanized by Resistance, the movement formed in opposition to the election of Donald Trump, the current cycle of mobilization in the United States is characterized by its recourse to nonviolent direct action and the re-actualization of civil disobedience. The practice was formally theorized in the 1960s by various political philosophers, among whom John Rawls figures prominently. Yet many contemporary political theorists criticize its institutionalization and challenge the hegemony of what has become the “Rawlsian consensus”. The present article outlines a brief intellectual history of the concept of civil disobedience in the US academic field. It shows how the liberal account – and Rawls’ in particular – became hegemonic, and why they are being contested. In presenting the current critics, this article points out that the notion is shaped by specific social, academic and political contexts and that, far from being stabilized and stabilizable, it is in constant evolution, torn between disciplinary debates and empirical and theoretical injunctions.